Carbono no solo e produtividade de grãos em sistemas de preparo e plantas de cobertura - Pasqualotto, Emanuel França (2025)
The dynamics of soil carbon (C) is directly influenced by the use of the area, mainly by the soil management method, sequence of crops used in the system and the contribution of residues. Based on this, the present study aimed to evaluate the effect of cover crops and soil management on grain yield and soil organic carbon stock in an Oxisol in Southern Brazil. The experiment is located at the Research and Innovation Center of the Rural Development Institute of Paraná (IDR-PARANÁ), in Pato Branco – PR. It has been conducted since 1986, so it has been 39 years with soil management systems, no-tillage (NT) and conventional tillage (CT) and the use of cover crops. For the present study, the following treatments were selected: Fallow (FW); intercropping of two species (TS) with hairy vetch (Vicia pilosa) and white oat (Avena sativa); and the intercropping of seven species (SS) formed by White Oat (Avena sativa), Rye (Secale cereale), Triticale (Tritico secale Wittmack), Forage Pea (Pisum sativum ssp. Arvense), Forage Turnip (Raphanus sativus L.), Hairy Vetch (Vicia Pilosa) and Canola (Brassica napus L.), in the two soil management systems (NT and CT), composing a 3x2 factorial, with three replications in randomized blocks. The interval for the cultivation of soybeans (2022-2023 harvest), winter cover crops (2023), corn (2023-2024 harvest) and off-season beans (2024) was considered. Dry mass evaluations were carried out for all crops and yield for grain crops. A trench of 40 cm deep, and lateral of 30 cm wide, was carried out, where the soil density was evaluated by the volumetric ring method in layers 0-5, 5-10, 10-20, and 20-30 cm, and on the other side the soil was collected at the same depths to determine the total stock organic carbon (SOC) of the soil. The highest accumulation of DM occurred with the TS intercropping, with 28370 kg ha-1. No-tillage showed the highest SOC in the superficial layer of the soil with 17.55 Mg ha-1, 81 % higher than the conventional tillage that obtained 9.58 Mg ha-1. In deeper layers, the CT got more stock.